Pelatihan Penyusunan Modul Ajar Siswa Sekolah Dasar Berbasis Kurikulum Merdeka - Salamah, Evi Rizqi; Eka Tiyas Rifayanti, Zuni; Trisnawaty, Wulan; Subaidah, Subaidah (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
Modules are teaching materials that can be used by teachers in providing material during learning. In addition, the module is a support for learning activities. Even so, many teachers still who cannot compile modules to assist them in teaching and developing their potential. Therefore, this independent curriculum-based teaching module preparation training activity will provide benefits for teachers and students. Teachers will be able to teach well with existing teaching materials and can improve the quality of educator skills, and students get structured and systematic material. The methods used in community service activities are discussions, lectures, questions and consultations. Lectures and discussions are conducted to convey material regarding learning modules in general, while consultations are held to assist in the preparation of modules carried out by teachers and resource persons. The impact of the mentoring module at SD IT Darul Ilmi is good for teachers. This is shown from the modules produced by the teacher that have been adapted to the needs of students. In addition, the teacher also has good teaching materials for delivering material and students can master the material provided well.